Tribocorrosion Behavior of LY12 Aluminum Alloy in Artificial Seawater Solution. Issue 6 (1st November 2020) - Jun, Chen; Bingli, Pan; Quanan, Li
Abstract: In this work, a systematic investigation was carried out to study the electrochemical and tribocorrosion behavior of LY12 aluminum alloy sliding against an Al2 O3 pin in artificial seawater, using a pin-on-disc tribometer combined with an in situ electrochemical workstation. The results revealed that the cathodic shift of open circuit potential and two order of magnitude increase in current density caused by rubbing can be confirmed. There was a general trend that the total material loss of LY12 aluminum alloy increased with an increase in applied potential, indicating the synergistic effect between wear and corrosion, thus resulting in accelerated material degradation. When the potential was below −0.4 V, wear-induced corrosion was negligible; however, corrosion-induced wear was high and increased significantly with an increase in potential. When the potential was above −0.4 V, wear-induced corrosion increased sharply with an increase in potential and corrosion-induced wear was dominant. The significant role of corrosion-induced wear in the increment of material degradation can be attributed to the formation of corrosion pits and fragment layers in the wear track at high potential.